TOXIC EFFECT OF THE ANTIPSYCHOTIC HALOPERIDOL ON LEMNA MINOR (GRIFF, 1851) (LILIOPSIDA, LEMNACEAE) AND DAPHNIA MAGNA (STRAUS, 1820) (CLADOCERA, DAPHNIIDAE) - Ildefonso-Rivera, Diego (2022)
In this bioassay, the sublethal and lethal toxicity of the antipsychotic haloperidol was determined on the species L. minor and D. magna using five doses of haloperidol for 48h (0.22 mg·L-1, 0.67 mg·L-1, 2 mg·L-1, 6 mg·L-1 and 18 mg·L-1). The half maximal effective concentration (EC ) found in L. minor was 11.19 50 mg·L-1, while the no observed effect concentration (NOEC) and lowest observed effect concentration (LOEC) was 6 mg·L-1 and 18 mg·L-1, respectively. In the case of D. magna, the EC and mean lethal 50 concentration (CL ) was 29.82 y 290.55 mg·L-1 at 24h and 1.83 mg·L-1 y 5.69 mg·L-1 at 48h respectively. 50 The NOEC at 24h and 48h was 2 mg·L-1, and the LOEC was 6 mg·L- 1. L. minor and D. magna are considered bioindicators due to their sensitivity to haloperidol, so their exposure to this drug could affect and cause a risk to aquatic communities.